Biological Evaluation of New Oxadiazole-Based Synthetic α-glycosidase Inhibitors for Hyperglycemia Management: A Research Study: New Oxadiazoles act as a-glycosidase inhibitor - Arefeh Khosravi; Gholamhassan Vaezi; Nazanin Pirooznia; Khosrou Abdi; Vida Hojati (Iranian Journal of Pharmaceutical Sciences, 2022)
The present study was conducted to investigate the hypoglycemic activity of 3,4,5-triphenyl-oxadiazole derivatives and its effects on liver, lung, and kidney function in streptozotocin (STZ)-induced diabetic rats. For this purpose, male Wistar rats were divided into four groups (n = 4). Diabetes was induced in four groups by a single dose of STZ at 65 mg/kg body weight, administrated intraperitoneal. After 28 days of treatment, fasting blood sugar (FBS) levels and other biochemical parameters such as cholesterol, triglycerides phosphorous, urea creatinine, etc. were measured. Also, the markers of liver and kidney function, such as urea, serum creatinine, aspartate aminotransferase, alanine aminotransferase, and gamma-glutamyl transferase levels were determined. The study showed that the 3,4,5-triphenyl-oxadiazole derivatives at 100 mg/kg body weight had a significant antidiabetic activity after 28 days of treatment as the FBS levels decreased significantly while the serum insulin levels increased. Moreover, a significant decrease in the liver and kidney function markers in treated rats indicated the protective effect of the 3,4,5-triphenyl-oxadiazole derivatives against liver and kidney damage. The serum concentrations were normal in the control and the healthy group treated with these derivatives. The results of this study showed that both derivatives can regulate hyperglycemia and complications of diabetes.